Avaliação clínica do uso ou não de antibiótico sistêmico nas cirurgias para instalação de implantes orais osseointegráveis unitários - Pimentel Neto, Gonçalo Sobreira (2007)
The purpose of this prospective, randomized controlled clinical trial, was to compare the use or not of sistemic antibiotics in unit titanio oral implant surgery. It has been selected 60 patients by the criteria of exclusion, where systemic pathologies (diabete mellitus, nephropathies, hepatic illness), use of immunosuppressive agents (chronic use of steroidal anti-inflamatory agents, chemotherapy, radiotherapy), or local pathologies (periodontal disease, hard or soft tissue disease) was excluded. The selected patients were randomly divided in 3 groups of 20 each (Control, Test I and Test II). The groups were underdivided in 2 groups with 10 patients each, where one under group received machined implants and another one received surface treaty implants (TiUnite Nobel Biocare). The groups was clinical avaliated, in postoperatory, how the development of infection, and in the second stage surgery, how the implant survival. The Control group received 1g amoxicillin as antibiotic prophylaxis 1 hour before surgery and 500 mg every 8 hours for 7 days postoperatively. The Test I groupe only received 1 g of amoxicillin 1 hour preoperatively as prophylaxys. And, The Test II group not received any systemic antibiotics prior or after surgery. All groups received steroidal anti-inflamatory (8mg of dexamethasone) 1 hour before the surgery. Chlorhexidine 0,12% mouthrinse was used 1 hour preoperatively and each 12 hours after the procedure for 7 days. Pain was controlled with 1g of acetaminophen every 6 hours, while discomfort was present. The patients were evaluated clinically after implant placement for the development of infection and at the second stage procedure for implant loss. Results showed no statistical difference for infection or implant loss (P > 0.9) between groups. The use of sistemic antibiotics did not influence complications in this sample.